Development of Chemistry Learning Performance Assessment Instruments: Systematic Literature Review - Hasibuan, Nurhalimah; Ariani, Winda; Nahadi, Nahadi (Universitas Pendidikan Mandalika, 2025)
Assessments that are generally carried out by teachers usually only focus on cognitive aspects, whereas assessments of cognitive, affective, and psychomotor aspects also need to be carried out. This study aims to develop a performance assessment instrument. Performance assessment is a form of authentic assessment that aims to improve learning and provide constructive feedback to teachers and students. Although it has many benefits, performance assessments are rarely carried out by teachers during learning due to the teacher's limitations in creating performance assessment instruments. Performance assessments can be in the form of product assessments and practice assessments. The research method used follows the PRISMA guidelines, namely by selecting articles from Google Search and Google Scholar. The results of the study showed that out of 121 articles, 9 articles met the criteria for further review. In conclusion, research on the development of performance assessments, especially in the field of chemistry, needs to be further developed. This has implications for the need for more effective developmental performance assessment instruments, especially in Indonesia, so that they can meet the needs of the current education curriculum.